FRI0375 SITE-SPECIFIC EFFECTIVENESS OF TNF INHIBITORS FOR ENTHESITIS IN DMARD-NAIVE PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (June 2019) - Huegle, Thomas; Moeller, Burkhard; Ciurea, Adrian; Nissen, Michael; Zueger, Patrick; Schulz, Martin; Ganz, Fabiana; Scherer, Almut; Papagiannoulis, Eleftherios
Abstract : Background: Enthesitis is a hallmark of spondyloarthritis (SpA), with substantial impact on quality of life. Although pathophysiological mechanisms of enthesitis may include both mechanical and autoimmune features, improvements upon initiation of TNF-inhibitors (TNFi) across individual enthesitis sites have not been reported in real-world patients with axial spondyloarthritis (axSpA). Objectives: To investigate the effectiveness of TNFi in axSpA patients without prior DMARD treatment at specific enthesitis sites, including spine, thoracic cage, Achilles tendon and the plantar fascia. Methods: This was a retrospective cohort study using the Swiss Clinical Quality Management in Rheumatic Diseases (SCQM) registry. AxSpA patients initiating TNFi without previous DMARD (biologic or conventional synthetic DMARD [csDMARD]) use and with available Maastricht Ankylosing Spondylitis Enthesitis Score, modified to include the plantar fascia, (MASES) at start of treatment ('baseline') and after 6 months (± 3 months) of follow up were included. Presence of enthesitis was defined as at least 1 inflamed enthesis. Among patients with any enthesitis present at baseline, the number of patients with enthesitis at each MASES site was assessed at baseline and the 6 month follow up. Fisher's exact test was used to assess significant enthesitis resolution at each enthesitis site between baseline and 6-month follow up. The Holm-Bonferroni method was used for multiplicity correction of p-values. Results: 781 DMARD-naive patients with axSpA who initiated TNFi were identified. At baseline, patients (57% male) were a median of 40 (interquartile range [IQR]) = 31-50) years of age with a median disease duration of 9 (IQR = 3-18) years and median Ankylosing Spondylitis Disease Activity Score (ASDAS-CRP) of 3.4 (IQR = 2.8-3.9) at treatment initiation. A subgroup of 160 TNFi patients had active enthesitis at baseline (MASES: mean = 4.14, standard deviation [sd] = 2.87) and a 6-month follow-up visit with MASES available (MASES: mean = 2.07, sd = 2.82), with a mean MASES reduction at the follow-up visit of 2.07 (sd = 3.06). At the 6-month follow up, complete enthesitis resolution was observed for 72 (45.0%) of patients. Enthesitis resolution was most frequent at the following sites: the costochondral sternum, the costochondral joint, the lumbar vertebra, the pelvic crest, and spina iliaca posterior (Figure 1 ). Limited resolution of enthesitis was observed in the spina iliaca anterior, plantar fascia, and the Achilles tendon. Conclusion: Our results suggest that for real-world DMARD-naïve axSpA patients, TNFi are generally effective for resolving enthesitis. Significant resolution was observed for enthesitis of the spine and thoracic cage though resolution was more limited for plantar fascia or Achilles tendon enthesitis. Lower limb entheses are more prone to mechanical strain and may therefore require alternative or more prolonged therapy. Acknowledgement: This study was funded by AbbVie Inc. All authors were involved in the study design, review, data interpretation and approval of the abstract. Disclosure of Interests: Thomas Huegle Grant/research support from: AbbVie, Lilly, Novartis and Pfizer, Speakers bureau: AbbVie, Lilly, Novartis and Pfizer, Burkhard Moeller Consultant for: Swissmedic Human Medicines Expert Committee Member (regulatory agency), Adrian Ciurea Consultant for: AbbVie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Michael Nissen Consultant for: AbbVie, Lilly, Novartis, and Pfizer, Patrick Zueger Shareholder of: AbbVie, Employee of: AbbVie, Martin Schulz Shareholder of: AbbVie, Employee of: AbbVie, Fabiana Ganz Shareholder of: AbbVie, Employee of: AbbVie, Almut Scherer Grant/research support from: Almut Scherer is an employee of SCQM, which receives funding from AbbVie, Celgene, iQONE, Lilly, MSD, Novartis, Pfizer, Roche, Sandoz, Sanofi Genzyme, and UCB., Consultant for: Consultant for Pfizer, MSD, and AbbVie, Eleftherios Papagiannoulis: None declared